The Use of the Self-Standing Turning Transfer Device to Perform Bed-To-Chair Transfers Reduces Physical Stress among Caregivers of Older Patients in a Middle-Income Developing Country - Goh, Choon Hian; Muslimah Y,; Ng, Siew-Cheok; Subramanian, Pathmawathi; Tan, Maw Pin (Frontiers in Medicine, 2014)
Manual transfer of elderly patients remains commonplace in many developing countries because the use of lifting equipment, such as hoists, are often considered unaffordable luxuries. The aim of this study was, therefore, to evaluate the usage and potential benefits of a low cost, mechanical turning transfer device among elderly patients and their caregivers on a geriatric ward in a developing country in South East Asia. Fifty-six inpatients, aged 66 to 92 years, on a geriatric ward, and their caregivers were recruited. Participants were asked to transfer from bed-to-chair transfer with manual assistance, and the task was repeated using the Self-standing Turning Transfer Device (STurDi). The time taken to perform manual transfers and STurDi-assisted transfers was recorded. Physical strain was assessed using the perceived physical stress-rating tool for caregivers with and without the use of the device. User satisfaction was evaluated using the USE questionnaire. There was a significant reduction in transfer-time with manual transfers compared to STurDi assisted transfers (mean(standard deviation) = 48.39(13.98) vs. 36.23(10.96);p=<0.001). The physical stress rating was significantly lower in STurDi-aided transfers compared to manual transfers, shoulder (median (interquartile range)= 0(1) vs. 4(3); p=0.001), upper back (0(0) vs. 5(4); p=0.001), lower back (0(1) vs. 5(3), p=0.001), whole body (1(2) vs. 4(3), p=0.001) and knee (0(1) vs. 1(4), p=0.001). In addition, majority of patients and caregivers definitely or strongly agreed that the device was useful, saved time, and was easy to use. We have therefore demonstrated in a setting where manual handling was commonly performed that a low-cost mechanical transfer device reduced caregiver strain and was well received by older patients and caregivers.